2016
DOI: 10.1002/jcb.25619
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Stress‐Responsive Transcription Factors Nrf2, ATF4, and AP‐1

Abstract: Cellular stress leads to an upregulation of gene transcription. We asked if there is a specificity in the activation of the stress-responsive transcription factors Nrf2, ATF4, and AP-1/c-Jun, or if activation of these proteins is a redundant cellular answer toward extracellular stressors. Here, we show that oxidative stress, induced by stimulation of the cells with the oxidant arsenite, strongly activated gene transcription via the stress-responsive element (StRE), while phorbol ester or tunicamycin, activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…He et al reported that ATF4 forms a heterodimer with Nrf2 and modulates HO-1 gene expression through binding to the stress-responsive element (StRE), which contains AREs, but not AARE [15]. However, it is controversial whether the Nrf2/ATF4 heterodimer directly transactivates HO-1 through StRE, since contradicting results were also reported, and the affinity of the Nrf2/ATF4 heterodimer to the StRE is significantly lower than that of the Nrf2/sMaf heterodimer [15,38]. Using ChIP analysis, Dey et al reported that Nrf2 and ATF4 are recruited to the StRE-containing HO-1 enhancers in a mutually dependent manner and cooperatively activate HO-1 gene expression upon cancer cells’ detachment from the matrix (i.e., anoikis) [39].…”
Section: Discussionmentioning
confidence: 99%
“…He et al reported that ATF4 forms a heterodimer with Nrf2 and modulates HO-1 gene expression through binding to the stress-responsive element (StRE), which contains AREs, but not AARE [15]. However, it is controversial whether the Nrf2/ATF4 heterodimer directly transactivates HO-1 through StRE, since contradicting results were also reported, and the affinity of the Nrf2/ATF4 heterodimer to the StRE is significantly lower than that of the Nrf2/sMaf heterodimer [15,38]. Using ChIP analysis, Dey et al reported that Nrf2 and ATF4 are recruited to the StRE-containing HO-1 enhancers in a mutually dependent manner and cooperatively activate HO-1 gene expression upon cancer cells’ detachment from the matrix (i.e., anoikis) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors mediate mitochondrial responses to stress, notably, Nrf2 ( 84 ), ATF4 ( 85 ), and other AP-1 paralogs. Although stressors that activate AP-1 via JNK have only minimal effects on Nrf2- or ATF4-induced transcription ( 86 ), this does not exclude the possibility of the converse. JNK can be activated by mitochondrial ROS in ischemia-reperfusion ( 87 ) or by the mtUPR ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…When mouse hepatoma cells are exposed to cadmium chloride - a potent inducer of HO-1, the ATF4-Nrf2 dimer binds to the ARE of HO-1 and activates its transcription. The ATF-Nrf2 dimer binds to the AREs depending on the nature of the stress stimulus [173] . During the induction of atherosclerotic vessels by oxidized phospholipids, Nrf2 upregulates ATF4 leading to the increased expression of vascular endothelial growth factor [174] .…”
Section: Transcription Factors That Interact With Aresmentioning
confidence: 99%